2017
DOI: 10.1016/j.chest.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Transbronchial vs Surgical Lung Biopsy in the Diagnosis of Suspected Fibrotic Interstitial Lung Disease

Abstract: Information from TBB, when combined with clinical and HRCT data, may provide enough information to make a confident and accurate diagnosis in approximately 20% to 30% of patients with ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 44 publications
1
65
1
3
Order By: Relevance
“…Prior studies have demonstrated characteristic findings of HP in only 11–25% of TBBx [19, 28, 29]. In contrast to prior studies, TBBx was characteristic of HP in 40.2% of all patients in our study who underwent TBBx and in 46.2% of patients who had < 20% BAL lymphocytes.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Prior studies have demonstrated characteristic findings of HP in only 11–25% of TBBx [19, 28, 29]. In contrast to prior studies, TBBx was characteristic of HP in 40.2% of all patients in our study who underwent TBBx and in 46.2% of patients who had < 20% BAL lymphocytes.…”
Section: Discussioncontrasting
confidence: 96%
“…Transbronchial biopsy (TBBx) can be diagnostic in certain forms of ILD, such as granulomatous lung disease [27]. While tissue obtained from TBBx may be inadequate or nondiagnostic [19, 28, 29], TBBx can be performed at the same time as the BAL and has the potential to confer additive information regarding diagnosis with only minimal increase in risk [30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have clearly shown that TBCx provides larger specimens with fewer artefacts (figure 2) than regular forceps transbronchial biopsies (TBBx). In our previously published series [30], we reported a sensitivity for UIP detected by TBBx of only 30% for expert pathologists, and these data have recently been confirmed in a study that found TBBx useful to reach a confident and accurate multidisciplinary diagnosis in only 20-30% of patients with DPLDs, with the majority of cases requiring surgical lung biopsy (SLB) to secure a definite diagnosis [31]. By contrast, TBCx specimens are largely comparable to SLB, although the TBCx diagnostic yield falls short of that for SLB (80% for TBCx versus >90% for SLB), so TBCx has the potential to remove the need for surgery for a large proportion of patients.…”
Section: Multidisciplinary Diagnosis Of Dplds: All That Glitters Is Nmentioning
confidence: 99%
“…Although conventional transbronchial biopsy has a low yield for the diagnosis of ILD (20–30%) , transbronchial cryobiopsy represents a promising intermediary technique. Cryobiopsy combines flexible bronchoscopy with a cryoprobe to remove biopsy specimens of >5 mm in size, a threshold that has been considered sufficient for a diagnosis of ILD.…”
Section: Introductionmentioning
confidence: 99%